2022
DOI: 10.3389/fonc.2022.1033413
|View full text |Cite
|
Sign up to set email alerts
|

Obinutuzumab plus chlorambucil versus ibrutinib in previously untreated chronic lymphocytic leukemia patients without TP53 disruptions: A real-life CLL campus study

Abstract: One of the main issues in the treatment of patients with chronic lymphocytic leukemia (CLL) deals with the choice between continuous or fixed-duration therapy. Continuous ibrutinib (IB), the first-in-class BTK inhibitor, and obinutuzumab-chlorambucil (G-CHL) are commonly used therapies for elderly and/or comorbid patients. No head-to-head comparison has been carried out. Within the Italian campus CLL network, we performed a retrospective study on CLL patients without TP53 disruption treated with IB or G-CHL as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…For unknown reasons, obinutuzumab-based treatment seems to be highly toxic in patients with anti-MAG neuropathy as compared with other real-world evidence studies in patients with CLL. 25 , 26 …”
Section: Resultsmentioning
confidence: 99%
“…For unknown reasons, obinutuzumab-based treatment seems to be highly toxic in patients with anti-MAG neuropathy as compared with other real-world evidence studies in patients with CLL. 25 , 26 …”
Section: Resultsmentioning
confidence: 99%
“…We found a higher reporting of atrial fibrillation with ibrutinib therapy. Accordingly, a retrospective study found a lower development of atrial fibrillation in patients affected by CLL treated with obinutuzumab plus chlorambucil than ibrutinib in spite of a not statistically significant difference (2% vs. 9%, p = 0.0813) ( Visentin et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…An indirect comparison of CIT with Chlor + O and ibrutinib was performed with the Italian CLL campus network [82]. Patients with TP53 disruptions were excluded.…”
Section: Real-world Evidencementioning
confidence: 99%